Cryopreservation of horse semen with a liposome and trehalose added extender - Medina-León, Ariadna Z.; Domínguez-Mancera, Belisario; Cazalez-Penino, Nicolás; Cervantes-Acosta, Patricia; Jácome-Sosa, Edelmira; Romero-Salas, Dora; Barrientos-Morales, Manuel (Austral Journal of Veterinary Sciences, 2019)
The aim of the study was to evaluate the effect of cryopreserved equine semen in the presence of trehalose-loaded liposomes on the integrity and function of sperm cells. Six ejaculations of five stallions collected with an artificial vagina were used. The ejaculates were diluted with INRA 96® 2:1 v/v and transported at 22 °C to the laboratory. Before cryopreservation, the semen was diluted with INRA Freeze® to obtain the following treatments: T1) INRA Freeze® (control), T2) INRA Freeze® + liposomes, T3) INRA Freeze® + liposomes+trehalose. Data were analysed using the Kruskal Wallis test. The percentages of sperm with intact DNA were 54.5, 57.9, and 64.8% for T1, T2 and T3, respectively (P>0.05). When evaluating the acrosomal and capacitation state after filtering with Percoll®, the percentages of spermatozoa without acrosome reaction and without capacitation were 67.8, 79.2 and 68.1% in T1, T2, and T3, respectively (P>0.05), while the capacitated sperm without acrosome reaction and without capacitation was similar in T1 (47%) and T3 (32%) (P>0.05), and lower in T2 (16%) before filtering with Percoll®. The use of liposomes and liposome-trehalose did not affect on the functional status and nuclear chromatin of the equine sperm after freezing, but it did affect the percentage of capacitated sperm without acrosome reaction after selecting the thawed semen using the Percoll® gradient.